Your environment air, air pollution, and weather - Henson, Collins M. (Danville, Ill. Interstate Printers & Publishers, 1971)
A text on the atmosphere which includes both basic facts and more complex scientific data on air, weather, and air pollution.
Keywords: Air; Weather; Air -- Pollution